(untitled) (Laisvalaikio tyrimai, 2018)
Theoretical substantiation. The article explores the recreational value and importance of working in human life, analysis of its association with human health and quality of life perception. Any human activity is motivated, so the analysis of effective leisure time, determined not only selected leisure activities, but also reveals the need for the factors, which determine the choice of such activities. The object of the survey was the choice of motivational factors in leisure. The aim of study was to assess the determining factors of leisure motivation of young working people Method. Organized research through a questionnaire based on L. G. Pelletier et al. (1991) leisure motivation scale. The sample consisted of 70 young working people from Kaunas city – 47 women and 23 men. The study investigated whether young working people have enough leisure time, what are its forms and conducting research to evaluate the disclosure of their health. In determining what are the key motivating factors behind the choice of leisure study comparing interpretations of gender and health research aspects of perception. The study data were processed on the basis of mathematical statistics Findings. The survey data suggests that young working people have more leisure time on weekends and often spends it passively (reading, watching television). Examination of the leisure motivation of the youth revealed that most strongly influenced by the choice of leisure internal motivation to experience stimulation, i. e., targeted to the inner satisfaction, enjoyable activities that stimulate feelings of certain associations. Youth groups, by gender dominated external motivation external regulation, external regulation motivation moved, the internal motivation to know, that is these groups of people belonging to an external reward or avoid an external punishment, reward or to avoid the inner interior penalty, to seek knowledge, explore, understand the relevant issues. The analysis of young people’s perceptions of their health status and the motivation of leisure activities to those persons who are unable to assess their health status is at least apathetic choosing forms of leisure and are sufficiently strong and determined to knowing what is going. Those persons who believe that there is poor health status in the form of leisure for engaging external motivation identified regulation – they are important leisure activities, and results are or will be useful, but it does not feel the inner satisfaction. Keywords: leisure, motivation, Self-determination Theory.